A Time Of Choosing: Conversion and Discernment in the Mind of Pope Francis - McEvoy, Tim (The way, 2020)
The article highlights the October 2018 issue of The Way, Austen Ivereigh suggests that Pope Francis 'sees in the tribulation and ferment of the Church an opportunity for patient conversion through a renewed humble and joyful dependence on God's mercy.'